Advanced Targeted Nanomedicine A Communication Engineering Solution - Chude-Okonkwo, Uche.; Malekian, Reza.; Maharaj, BT.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents medical challenges as communication engineering problems. It offers the reader the interesting perspective of exploring and understanding disease pathology from the point of view of communication engineers. Therefore, diseases and their treatments can be addressed using conventional communication paradigms, approaches, tools and devices; thereby ushering in the interdisciplinary research platform termed advanced targeted nanomedicine. The rudimentary framework for advanced targeted nanomedicine is presented and expatiated across the seven chapters of this book.
Communication Engineering meets Medical Science: The Advanced Targeted Nanomedical Solution -- Communication between Living and Non-Living Systems: The Basis for Advanced Targeted Nanomedicine -- Nanosystems and Devices for Advanced Targeted Nanomedical Applications -- Understanding Delivery Routes and Operational Environments of Nanosystems -- Classical Framework for Case-driven Design of Advanced Targeted Nanomedical Solution -- Internet of Things for Advanced Targeted Nanomedical Applications -- Discussion on Advanced Targeted Nanomedical Application Scenarios for Treatment of Some Chronic Diseases.
Keywords: Nanotechnology; Biomedical engineering; Telecommunication; Nanotechnology; Biomedical Engineering and Bioengineering; Communications Engineering, Networks